Association between history of psychosis and cardiovascular disease in bipolar disorder. (9th June 2015) - Prieto, Miguel L; McElroy, Susan L; Hayes, Sharonne N; Sutor, Bruce; Kung, Simon; Bobo, William V; Fuentes, Manuel E; Cuellar‐Barboza, Alfredo B; Crow, Scott; Ösby, Urban; Chauhan, Mohit; Westman, Jeanette; et al.
<x xml:space="preserve">Abstract</x> Objectives To determine whether clinical features of bipolar disorder, such as history of psychosis, and cardiovascular disease (CVD) risk factors contribute to a higher risk of CVD among patients with bipolar disorder. Methods This cross‐sectional study included a sample of 988 patients with bipolar I or bipolar II disorder or schizoaffective bipolar type confirmed by the Structured Clinical Interview for DSM‐IV‐TR disorders (SCID). Medical comorbidity burden was quantified utilizing the Cumulative Illness Severity Rating Scale (CIRS). This 13‐item organ‐based scale includes cardiac disease severity quantification. Confirmed by medical record review, patients who scored 1 (current mild or past significant problem) or higher in the cardiac item were compared by logistic regression to patients who scored 0 (no impairment), adjusting for CVD risk factors that were selected using a backwards stepwise approach or were obtained from the literature. Results In a multivariate model, age [odds ratio (OR) = 3.03, 95% confidence interval (CI): 1.66–5.54, p < 0.0001], hypertension (OR = 2.43, 95% CI: 1.69–3.55, p < 0.0001), and history of psychosis (OR = 1.48, 95% CI: 1.03–2.13, p = 0.03) were associated with CVD. When CVD risk factors from the literature were added to the analysis, age (OR = 3.19, 95% CI: 1.67–6.10, p = 0.0005) and hypertension (OR = 2.46, 95% CI: 1.61–3.76, p < 0.01) remained significant, with psychosis being at the trend level (OR = 1.43, 95% CI: 0.96–2.13, p = 0.08). Conclusions The phenotype of psychotic bipolar disorder may reflect higher illness severity with associated cardiac comorbidity. Further studies are encouraged to clarify the effect of the disease burden (i.e., depression), lifestyle, and treatment interventions (i.e., atypical antipsychotics) on this risk association.